HUBUNGAN KESEIMBANGAN TOTAL BAKTERI ASAM LAKTAT DAN Escherichia coli DENGAN STATUS GIZI PADA ANAK SEKOLAH DASAR DI KALIBAWANG KABUPATEN KULON PROGO - , NI`MAH HANIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Malnutrition is a major problem in developing countries. Malnutrition affects the immune system and associated with higher susceptibility to infection. Infectious disease associated with the presence of pathogenic microflora. Normal microflora can be found in human body. Gut microflora play role to maintain human health. Gut microflora influence human metabolism and immune system. Objective : To investigate the association between lactic acid bacteria and Escherichia coli with nutritional status in elementary school children. Methods : This study was an observational cross-sectional research design. Subjects consisted of 30 students of grade 3 â 5 from SD Negeri 1 Dekso, Kalibawang, Kulon Progo. Total LAB and E. coli from fecal samples were determined using Total Plate Count method on MRS agar media for LAB and TBX agar media for E. coli. Nutritional status was measured anthropometrically (height and weight) using BMI for age index. Measurement of food intake with 3 times 24 hours food recall. Results : 73,3% subject classified with normal nutritional status. The highest total LAB was found in subject with overweight and obesity. The lowest total E. coli was found in subject with normal nutritional status. LAB was more abundant than E. coli in normal nutritional status (107 dan 106 CFU/g). But there was no significant association between total LAB, E. coli with nutritional status (p=0,40 and p=0,25). Most subjects have good energy intake (66,7%). Energy intake was associated with nutritional status (p=0,01). Conclusion : There was no association between total lactic acid bacteria and E. coli with nutritional status in elementary school children.